Pengaruh Penggunaan Tray Dryer Pada Proses Pengeringan Daun Kelor Terhadap Karakteristik Kimianya: Kajian Suhu: Drying Characteristics of Moringa Oleifera Leaves Using a Tray Dryer Machine at Various Temperature Levels - Meilita, Reti; Tanggasari, Devi (Universitas Bumigora, 2023)
Moringa oleifera is a plant commonly found in tropical and subtropical regions such as Indonesia. Minimum utilization of Moringa leaves is one of the problems amid the abundant availability of Moringa leaves. Drying process using a tray-dryer (rack-type drier) is one suitable method for handling moringa leaves. This study aimed to determine the effect of using a tray dryer on the reseach parameters; moisture contect, relative humidity, drying rate and moisture ratio. The method in this study, a one-factor completely randomized design (RAL) was used with 3 treatments (45℃, 50℃ and 55℃)with a drying time of 1 hour. Research data were analyzed using SPSS. The results showed that the drying temperature had a significant effect on moisture content, relative humidity, drying rate, moisture ratio. The best treatment was at a drying temperature of 55℃ which resulted in a moisture content value of 27,56%, a relative humidity of the drying chamber of 32,20%, a drying rate of 0,148 kg/s, and a moisture ratio of up to 0.